The Effect of Occupational Safety and Work Environment on Employee Performance - David Agung Sinatha; Sunan Trioko; Ghina Nabilah (Kirana Publisher (KNPub), 2026)
Employee performance is one of the primary determinants of organizational success, particularly in companies operating in high-risk industries such as electricity services. This study aims to analyze the influence of occupational safety and health and the work environment on employee performance at PT PLN (Persero) ULP Sutojayan, Blitar Regency. This research employed a quantitative explanatory approach involving all 70 employees as respondents using a census sampling technique. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression, supported by validity, reliability, classical assumption, t-test, F-test, and coefficient of determination analyses. The findings reveal that occupational safety and health significantly improve employee performance. Likewise, the work environment has a positive and significant effect on employee performance. Simultaneously, both variables contribute significantly to employee performance improvement. These findings indicate that an effective occupational safety management system combined with a supportive work environment enhances employee productivity, work quality, and organizational performance. The study contributes empirical evidence regarding human resource management in the electricity service sector and provides managerial implications for strengthening workplace safety culture and creating conducive working conditions